Please, Louise - Wishinsky, Frieda (Groundwood Books, 2007)
Jake is annoyed that his little sister Louise won't leave him alone. He wishes Louise were a dog. Suddenly Louise is gone and a little dog appears to be in her place. Jake is worried that his wish may have come true.